2001
DOI: 10.1259/bjr.74.883.740642
|View full text |Cite
|
Sign up to set email alerts
|

MR diffusion tensor imaging of white matter tract disruption in stroke at 3 T

Abstract: Recent advances in MR diffusion weighted imaging (DWI) enable the identification of anisotropic white matter tracts with diffusion tensor imaging (DTI). We aimed to use a novel DTI technique to safely study patients with recent stroke in a high field (3 T) MR machine with its intrinsically higher spatial resolution and signal-to-noise ratio. Of ten patients studied, six had disruption of white matter tracts as determined by DTI. A further patient had distortion of white matter tracts around an infarct rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 31 publications
1
28
1
Order By: Relevance
“…Clarification of the cause of motor weakness is essential for prognosis and for adoption of scientific strategies for successful rehabilitation [22][23][24][25][26]. Recovery following a stroke is typically classified into neurological recovery and functional recovery; functional recovery is influenced by the external environment, continuity of rehabilitation, and motivation, whereas neurological recovery varies according to stroke pathogenesis and lesion site [27].…”
Section: Correlation Between Brain Lesion and Motor Recoverymentioning
confidence: 99%
“…Clarification of the cause of motor weakness is essential for prognosis and for adoption of scientific strategies for successful rehabilitation [22][23][24][25][26]. Recovery following a stroke is typically classified into neurological recovery and functional recovery; functional recovery is influenced by the external environment, continuity of rehabilitation, and motivation, whereas neurological recovery varies according to stroke pathogenesis and lesion site [27].…”
Section: Correlation Between Brain Lesion and Motor Recoverymentioning
confidence: 99%
“…This is in contrast with metastases, which tend to spread along vascular planes and form a tumour that is separate from the surrounding brain. Diffusion tensor imaging (DTI) is very sensitive in detecting disruption of white matter in regions that appear normal in a number of diseases [31][32][33][34][35]. Initial studies in brain tumours have shown a 30 u deviation of corona radiata fibres in a patient with a low-grade glioma, suggesting that the fibres had been displaced but not infiltrated by the tumour [36].…”
Section: Imaging White Matter Disruptionmentioning
confidence: 99%
“…In addition to damage to gray matter structures, white matter vulnerability is observed in both ischemic (Dewar et al, 2003;Gillard et al, 2001;Pantoni et al, 1999) and traumatic Gentleman et al, 1995;Maxwell et al, 1993;Strich, 1961) conditions. Because the normal function of the brain is dependent on the communication between brain regions, the clarification of mechanisms contributing to acute and/or progressive white matter damage is critical to our understanding of brain injury (Goldberg and Ransom, 2003).…”
Section: White Matter Vulnerabilitymentioning
confidence: 99%